Farklı lise türlerine göre öğretmen ve öğrencilerin okul kültürü metaforu algıları - Mukadder, Özan Boydak.; Canan, Demir. (My University, 2011)
Bu çalışmanın amacı, Türkiye'nin doğusunda bulunan Muş ilindeki farklı lise türlerine göre öğretmen ve öğrencilerin "okul kültürü" ile ilgili algılarını metaforlar aracılığıyla belirlemektir. Bu amaç doğrultusunda, öğretmen ve öğrencilerden okul kültürünü en iyi tanımlayan metaforlar araştırıldı. Farklı okul türlerine göre algıları belirlemek amacıyla metaforlar 11 imge altında toplandı ve frekans dağılımları analiz edildi. Endüstri Meslek Lisesi, Kız Meslek Lisesi, Anadolu Lisesi ve Genel Lise'de öğrenim gören toplam 213 öğrenci ve bu liselerde görev yapan 46 öğretmen araştırmanın örneklemi olarak seçildi. Yarı yapılandırılmış açık uçlı soru formatmda elde edilen cevaplar analiz edildi. En sık kullanılan metafor, "aile" metaforu olmuştur ve öğretmenlerle öğrencilerin okul kültürüne yönelik algılarında farklılıklar olduğu göze çarpmıştır.

The purpose of this study is to determine the perceptions related to -school culture- of students and teachers from different types of high schools through metaphors in the province of Muş, the east of Turkey. For this purpose, it has been researched that which metaphors are used by the teachers and the students to describe school culture best. In order to determine the perceptions of different schools types, the metaphors have been piled under 11 images and the frequency distributions have been analyized. 213 students and 46 teachers from Industrial Vocational School, Girls Vocational School, Anatolian School and Cumhuriyet (General School) that are located in the province of Muş in 2008-2009 academic years were chosen as the working group of the study. The answers given to the semi-structured and open-ended question forms were analyzed. The mostly used metaphor is -family- and there are some differences between students and teachers' perceptions.
The Perceptions of Students and Teachers Related to School Culture Metaphor According To Different High Schools
Keywords: Tarih